(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract The aim of the research is to measure the effect of changing the exchange rate on bank loans, and in order to achieve this goal, the (official exchange rate) was chosen as an independent variable and its effect was studied on the dependent variable, which is bank credit. Commercial Gulf, Baghdad, A Shore International for Investment (and the financial indicators (growth rate of loans) and the statistical program (Eviews 12) were used to measure the impact of the exchange rate change on the bank credit of banks, the research sample for the period 2012-2022, and the research reached a group Among the conclusions, the most important of which is that the results of the financial analysis of variables during the years of study showed that there was a discrepancy in the proportions of financial indicators, as they were characterized by fluctuations, ups and downs, which indicates a weak effect of the exchange rate on bank loans